The Development of Flash-Based Media in Project Based Learning for English Subject to Increase Students’ Motivation and Achievement at Senior High School - Trisyagil, Trisyagil; Ahmadi, Farid; Kustiono, Kustiono (Innovative Journal of Curriculum and Educational Technology, 2020)
The use of technology-based media increases students’ motivation and learning effectivity in the classroom. This research aims to develop, to examine the appropriateness and the effectivity of flash-based media at Senior High School. This development research uses the ADDIE model. Based on the research result, the score of validity trials from the material expert is 72, the score from the media expert is 58 and from the practitioner expert is 75. The assessment from the material, media and practitioner expert show that flash-based media is in the appropriate category. Effectiveness test of the flash-based media development is through the testing of hypothesis, the data shows that for both experimental and controlled class in pre-test and post-test, the score is Sig. (2-tailed) 0.000 < 0.05, and the score of the students’ motivation in learning for pre-test and post-test in both experimental and controlled is Sig. (2-tailed) 0.000 < 0.05. It means that the flash-based media increases students’ motivation and achievement in the learning process. This research result supports the theories of technology learning, especially for the development of learning aids and media for English subject.